Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Berpikir Kritis Siswa dalam Pelajaran Matematika di Kelas IV SDN 3 Sumber - Defi Agustiaputri; Fikriyah Fikriyah; Susilawati Susilawati (CV. ULIL ALBAB CORP, 2024)
This study aims to enhance the critical thinking skills of fourth-grade students at SD Negeri 3 Sumber by implementing the Problem Based Learning (PBL) model in mathematics, specifically on the topic of plane geometry. Conducted as Classroom Action Research (CAR), the study was structured into two cycles, each consisting of planning, action, observation, and reflection phases. The research subjects were 22 students, consisting of 9 girls and 13 boys. The study found that prior to the intervention, students had basic critical thinking skills, but lacked adequate stimulation. Through the implementation of the PBL model, there was a significant improvement in students' engagement and critical thinking skills, as evidenced by an increase in the percentage of critical thinking indicators from the pre-cycle stage to the second cycle. Initially, only a small percentage of students demonstrated critical thinking skills, which increased considerably after the implementation of PBL, showing that students became more active in expressing their ideas and opinions. The study also noted the improvement in the teacher's ability to facilitate PBL, contributing to the enhanced learning outcomes. This research concludes that the PBL model effectively develops students' critical thinking skills and suggests broader implementation in various educational contexts.